Asian functional foods - Shi, John (CRC Press, 2005)
Asian Functional Foods analyzes the biochemistry, nutrition, physiology, and food technology for a wide range of Asian foods. Fundamental introduction begins with the source, history, functionality, chemical, physical, and physiological properties of foods, followed by their health benefits, mechanisms of antioxidant action, anti-cancer and anti-aging properties, and clinical and epidemiological evidence. The book also details processing technology and systems, equipment, preparation, and quality control. Other topics include stability, shelf life, and storage technology, industrial production, home-made products, consumer and marketing issues, and social and economical issues.